2012
DOI: 10.1002/ep.11663
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of benzene as a surrogate tar in a gliding Arc plasma

Abstract: The pyrolysis and gasification technology uses diverse waste resources, including biomass, urban solid waste, and sewage sludge, to produce synthetic gases for industrial use. The tar in the thermal decomposition gas from the pyrolysis and/or gasification process, however, damages synthetic gas facilities and causes operation trouble. In this study, a gliding‐arc plasma reformer for tar decomposition was developed to address the aforementioned problem. In addition, experiments were performed on the variables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 20 publications
(58 reference statements)
7
22
0
Order By: Relevance
“…(1) Figure 5 indicates that as the moisture concentration increases, the destruction efficiency of toluene, naphthalene, and phenanthrene increases first to a maximum at a moisture concentration of 8% or 12% and then starts decreasing. Previous studies by Zhu et al [36] and Chun et al [39] showed a similar phenomenon for the decomposition of tar surrogate using gliding arc. The proper amount Figure 5 indicates that as the moisture concentration increases, the destruction efficiency of toluene, naphthalene, and phenanthrene increases first to a maximum at a moisture concentration of 8% or 12% and then starts decreasing.…”
Section: Co + H2o→co2 + H2supporting
confidence: 64%
See 1 more Smart Citation
“…(1) Figure 5 indicates that as the moisture concentration increases, the destruction efficiency of toluene, naphthalene, and phenanthrene increases first to a maximum at a moisture concentration of 8% or 12% and then starts decreasing. Previous studies by Zhu et al [36] and Chun et al [39] showed a similar phenomenon for the decomposition of tar surrogate using gliding arc. The proper amount Figure 5 indicates that as the moisture concentration increases, the destruction efficiency of toluene, naphthalene, and phenanthrene increases first to a maximum at a moisture concentration of 8% or 12% and then starts decreasing.…”
Section: Co + H2o→co2 + H2supporting
confidence: 64%
“…The proper amount Figure 5 indicates that as the moisture concentration increases, the destruction efficiency of toluene, naphthalene, and phenanthrene increases first to a maximum at a moisture concentration of 8% or 12% and then starts decreasing. Previous studies by Zhu et al [36] and Chun et al [39] showed a similar phenomenon for the decomposition of tar surrogate using gliding arc. The proper amount of moisture facilitates the reaction because of the generation of OH radicals [40], while too much water has an adverse effect on tar destruction due to its electronegative characteristics, which limits electron density and quenches reactive species [30].…”
Section: Co + H2o→co2 + H2supporting
confidence: 64%
“…Number of gaseous components entering a reactor-similar to a real biomass producer gas, which was considered only in [9,21]; 2. Number of tar components-in this work 3 tar representatives were used together while in most cases only 1 or 2 are used [11,15,16,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Excluding a few works performed on real biomass producer gas [9,14,21] only Kong et al [17], Eliott et al [10], Jamroz et al [12] and Yu et al [35] used at least 3 tar components, but in nitrogen, argon and oxygen as a plasmaforming gas; 3.…”
Section: Non-thermal Plasma Reactor and Processed Gasmentioning
confidence: 99%
“…A gas injection nozzle (inner diameter, 1.6 mm) was fixed onto the supporter at the top centre of the electrode. [15] An orifice baffle was installed at 20 mm from the bottom of the electrode preventing the plasma discharge interference. The orifice baffles were used for three different shapes which were named Type 1, Type 2, and Type 3 in Figure 2.…”
Section: Experimental Apparatusmentioning
confidence: 99%